CAPACITY OF PHYSICAL AND NON-PHYSICAL CHARACTERISTICS IN PREDICTING OBJECTIVE FUNCTION OF WOMEN WITH PATELLOFEMORAL PAIN - da Silva, Théo Muniz de Souza Borges [UNESP]; Perez, Vitoria Ozores [UNESP]; Waiteman, Marina Cabral [UNESP]; dos Santos Lopes, Helder [UNESP]; Briani, Ronaldo Valdir [UNESP]; de Azevedo, Fábio Mícolis [UNESP] (Elsevier, 2024)
Background Patellofemoral pain (PFP) is a chronic musculoskeletal disorder characterized by an insidious and diffuse pain around and/or behind the patella. People with PFP have decreased levels of physical activity and muscle strength of the knee extensors, as well as higher levels of pain, kinesiophobia, and body mass index (BMI). In addition, people with PFP experience decreased performance during objective function tests, such as the single leg hop test (SLHT). Although, theoretically, all the alterations above mentioned may be contributing to the decreased SLHT performance of individuals with PFP, no study has investigated this to date. Objectives To determine the capacity of physical activity level, BMI, pain level, kinesiophobia and muscle strength of knee extensors in predicting SLHT performance of people with PFP. Methods Sixty-two women with PFP were included in this study. Demographic data, level of physical activity (Baecke questionnaire), kinesiophobia (Tampa Scale) and average pain in the previous month (Visual Analogue Scale – 0 to 100 mm) were obtained. The objective function was evaluated with the SLHT, in which participants were required to hop forward as far as possible and the distance in centimeters was obtained. The concentric strength of the knee extensors was obtained with an isokinetic dynamometer at 60°/s. A multiple linear regression was performed to determine the capacity of muscle strength, kinesiophobia, BMI, pain and the level of physical activity in predicting the objective function of women with PFP. Results None of the independent variables (i.e., concentric knee extensor strength, Kinesiophobia, Pain, Physical activity level, BMI) were able to significantly predict the SLHT performance of women with PFP (F(5.56)=0.328; p=0.884; R2=0.028). Conclusion Despite the theoretical plausibility, the variables investigated in this study were not able to significantly predict the SLHT performance of women with PFP. It is possible that other variables not investigated in this study, such as the strength of the hip extensors, and the rate of torque development of the knee flexors and extensors may present with better predictive capacity. However, future studies are needed to confirm or refute this hypothesis. Implications As none of the variables were able to explain the performance of women in SLHT, it remains inconclusive why they present a decreased performance on this task compared to asymptomatic individuals.